Formação do Enfermeiro para atenção básica: análise da orientação teórica, cenários de prática e orientação pedagógica a partir de um curso de graduação - Brito, Maria da Conceição Coelho (2014)
Health professionals should be more involved with the various faces and interfaces that influence individuals and collectivities. In that purpose, the nurses must begin to understand this phenomenon from graduation, requiring a transposition of the physical limits of the universities, in order to lead students to a theoretical-practical interaction. Proposals for professional reorientation were being urged for years in this directionality. In the field of health, the last and current institutional proposal is the Pro-health. Thereby, this study aimed to analyze the formation of nurses for performance in basic attention, in the undergraduate program in nursing at the State University of Acaraú, according to the axes guiding Pro-health: theoretical orientation, practical scenarios and pedagogical orientation. This is a descriptive-exploratory study, quantitative and qualitative approach, carried out between 2012 and 2014, having as units of analysis the Pedagogical political project and Biannual Program Teacher of the course, students (27), teachers (13) and nurses preceptors (13) of the boarding school in the basic attention. The data collection was carried out through documentary analysis, questionnaire and interviews, in which they adopted the triangulation of methods such as methodological referential in collection and analysis, and thematic analysis of the data organization Minayo. A research project approved by the Research Ethics Committee (CEP) Valley State University of Acaraú (UVA). The results inferred allowed to verify compliance with aspects of the formation of the nurse for basic care at UVA on the basis of the Pro-health, how the modular structure, the encouragement of research practice, the progressive insertion in the field of practice since the beginning of the training, and the use of active methodologies in teaching-learning process, configuring the logic of "learning by doing". It was noted that the need to strengthen the teaching-service integration experienced in the formation of the nurse of the grape. Becomes necessary to critical discussion and reflective about the practice by all participants in the process (teachers, professionals, students services) for the processing of own practice and the management of the organizations involved, in order to strengthen training of nurses to the SUS.